Hydrothermal carbonization, torrefaction and slow pyrolysis of Miscanthus giganteus. (1st December 2017) - Wilk, Małgorzata; Magdziarz, Aneta
Abstract: The main aim of the paper is to analyze the effect of different pretreatment processes (HTC, torrefaction and slow pyrolysis) on the properties of Miscanthus giganteus . In this study, the HTC process was conducted in a Zipperclave Stirred Reactor under following parameters: temperature (180, 200 and 220 °C), pressure (<2.5 MPa) and residence time (2, 3, 4, 6, and 12 h). The effect of temperature and residence time of torrefaction and slow pyrolysis were studied in specially designed laboratory apparatus. Torrefaction temperature was held at 230, 260, and 290 °C, and residence time was specified for 0.5, 1.0 and 1.5 h. The preliminary study for slow pyrolysis processes were performed at 350, 400, 450 and 500 °C for 0.5, 1.0 and 1.5 h. The thermal behaviour of raw and pretreated Miscanthus was investigated by TGA analysis. Finally, HTC, torrefaction and slow pyrolysis processes proved an improvement in the combustible characteristics of the obtained biochars compared to raw biomass by the spectacular increase of carbon content 36%, 34% and 80%, respectively. Highlights: The pre-treatment processes of Miscanthus x giganteus were investigated. The effect of temperature and residence time on hydrothermal carbonization, torrefaction and slow pyrolysis was studied. The physical and chemical properties of raw, hydrochars, torrefied Miscanthus and pyrochars were determined. The thermal behaviour of raw and pretreated Miscanthus was investigated by TGA analysis.